The Limits of Bureaucratic Efficiency. - Prendergast, Canice (Journal of Political Economy, 2003)
Bureaucracies tend to be used when consumers cannot be trusted to choose outcomes efficiently. But a primary means of bureaucratic oversight is consumer complaints. But this can give bureaucrats an incentive to inefficiently accede to consumer demands to avoid a complaint. I show that when this incentive is important, bureaucracies (efficiently) respond by (i) ignoring legitimate consumer complaints, (ii) monitoring more in situations in which it is not needed, (iii) delaying decision making “too long,” and (iv) biasing oversight against consumers. I also show that bureaucracies are used only when consumers cannot be trusted. As a result, observed bureaucracies are always inefficient. Reprinted by permission of the publisher.